The influence of inventory management practice on firms’ competitiveness and organizational performance - EWUNTOMAH IDDISAH ABDULAI (KNUST, 2024)
A thesis submitted to the department of supply chain and information systems in partial fulfillment of the requirements for the degree of master of science (logistics and supply chain management)